KUALITAS PELAYANAN, HARGA DAN CITA RASA DALAM MENINGKATKAN KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA WARUNG RAWON DAN SOTO BANYUWANGI DI KELURAHAN KOTAKULON, BONDOWOSO - Septianingrum, Nurul Aini; Tulhusnah, Lusiana; Pramitasari, Triska Dewi (Fakultas Ekonomi dan Bisnis, 2025)
Competition in the culinary sector is becoming increasingly intense, including in areas such as Bondowoso. Traditional food stalls like Rawon and Soto Banyuwangi play an important role in attracting customers through their distinctive taste and local cultural uniqueness. This study aims to analyze the influence of service quality, price, and taste on customer satisfaction, both directly and indirectly through purchase decision as an intervening variable. The sampling technique was conducted through questionnaire distribution. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM) approach. The results of the direct effect hypothesis test using SmartPLS 3.2.8 application show that service quality has a significant positive effect on purchase decision, price has a significant positive effect on purchase decision, while taste has a positive but not significant effect on purchase decision. Furthermore, service quality has a positive but not significant effect on customer satisfaction, price has a positive but not significant effect on customer satisfaction, and taste has a negative and not significant effect on customer satisfaction. Meanwhile, purchase decision has a significant positive effect on customer satisfaction. The results of the indirect effect hypothesis testing indicate that service quality has a significant positive effect on purchase decision through customer satisfaction, price also has a significant positive effect on purchase decision through customer satisfaction, while taste has a positive but not significant effect on purchase decision through customer satisfaction.